2015
DOI: 10.1002/sim.6736
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of prevalence‐based incidence estimation techniques with application to dementia data in Germany

Abstract: Dementia is becoming a major health burden, which is mainly due to the increasing life expectancy in many developed countries. To describe the disease progression of individuals, multistate models are generally appropriate tools. These models allow the individuals to move along a path consisting of a finite number of disease states. We consider a simplifying illness-death model in which the subjects progress through the states healthy, diseased and dead. We use this model to study analytic relationships betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The estimation of the age-specific incidence is accomplished indirectly via a mathematical method, which has demonstrated higher accuracy compared with all hitherto existing methods of incidence estimation from prevalence data 14. By the epidemiological rule that the prevalence equals the product of the mean incidence and the mean duration, it can be shown that our estimated incidence rate is consistent with the prevalence data (see the online supplementary file for details).…”
Section: Discussionmentioning
confidence: 80%
“…The estimation of the age-specific incidence is accomplished indirectly via a mathematical method, which has demonstrated higher accuracy compared with all hitherto existing methods of incidence estimation from prevalence data 14. By the epidemiological rule that the prevalence equals the product of the mean incidence and the mean duration, it can be shown that our estimated incidence rate is consistent with the prevalence data (see the online supplementary file for details).…”
Section: Discussionmentioning
confidence: 80%
“…Hence, the consequences in practical epidemiology are presumably small. In addition, it has recently been shown that, for the task of estimating incidence rates from prevalence data, methods based on ODEs, like the one presented in this article, are superior compared to other methods [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The applicability of the illness-death model for extracting incidence density estimates from prevalence and mortality data has been demonstrated previously for chronic diseases such as renal replacement therapy [ 24 ], dementia [ 25 ], and diabetes [ 26 ]. The present study adds to previous information by replicating the model in a non-Caucasian population and accounting for the remission rate of a chronic disease.…”
Section: Discussionmentioning
confidence: 99%